Students’ Perceptions of Collaborative Learning and its Impact on Academic Achievement - Gautam, Koshal Raj (Journal of Musikot Campus, 2025)
This descriptive survey research explores students’ perceptions of collaborative learning and its impact on academic achievement. The objective of the study is to examine students’ views on collaborative learning practices, identify commonly used collaborative techniques in the classroom, and assess the perceived impact of these methods on their academic performance. The study was conducted among 70 Grade 12 students from three institutional schools in Rupandehi district, Nepal. Data were collected using a structured and adapted questionnaire, administered to participants selected through random sampling. The findings reveal that students hold a generally positive perception of collaborative learning, recognizing it as a method that fosters a supportive, interactive, and engaging educational environment. Students highlighted increased motivation, better peer communication, enhanced critical thinking, and improved academic performance as key outcomes of collaborative learning. Moreover, the results suggest that when teachers effectively implement collaborative strategies—such as group discussions, peer feedback, and cooperative projects—students tend to participate more actively and achieve deeper understanding of the subject matter. These findings underscore the pedagogical value of collaborative learning and imply that its systematic integration into classroom instruction can play a significant role in enhancing students’ academic achievement. The study recommends that educators and institutions consider adopting collaborative approaches more intentionally to improve learning outcomes and foster academic growth.